Improving Students' Ability to Pronounce Arabic Sounds Through a Gradual Qur'an Recitation Program - Ridha Darmawaty; Fitri Fitri; Siti Muflichah; Arif Rahman Hakim (Jurnal Alsinatuna, 2022)
This study focuses on the problems in pronouncing Arabic letters and reading Arabic texts encountered by Arabic students at the Department of Arabic language who graduated from public secondary schools. To address these issues, researchers experimented with the simulation approach utilizing a gradual recitation program of the Qur'an from easy to complex, rarely heard, and listening to well-known verses. This research aimed to identify the simulation in the gradual Qur'an recitation program suitable for promoting the ability to articulate Arabic sounds for third-year students using Classroom Action Research (CAR). Kurt Lewin proposed the research design with planning, action, observation, and reflection procedures. The researchers completed the simulation procedure by listening to multiple repetitions of well-known verses utilizing a gradual Qur'an recitation program. The findings of this study were that the method in the present study, in which the researchers use Qur'an recitation with a simple rhythm and design the familiar verses, is appropriate to improve the students' ability to pronounce sounds.